Análisis metataxonómico de la fermentación espontánea de cacao de fino aroma en dos granjas industriales, Colombia (2021)
Fine aroma cocoa is high-quality cocoa characterized by unique flavor and aroma attributes. Only 5% of cocoa globally belongs to this category, and it is highly valued in the agro-industrial industry for its properties. In Colombia, it is intended to study more about the conditions and presence of metabolites produced by microorganisms during the fermentation of fine aroma cocoa; that can trigger unique sensory characteristics. Therefore, this study focused on the microbiological identification and possible organoleptic characteristics of the predominant groups found, for two different cocoa farms, located in Arauca and Necoclí, Colombia. For this, metataxonomic data of the 16S rRNA and ITS marker genes were used to characterize bacteria and fungi, respectively. A methodological protocol was established to carry out these studies in the future, considering possible sampling and sequencing errors presented with the treated data. The presence and dominance in both farms of yeasts, acetic acid bacteria (AAB), and sporulated bacteria were determined. Likewise, a reduced presence of lactic acid bacteria (LAB) was found in comparison with the other groups and its previous reports in the literature. As result, a prevalence of Acetobacter pastorianus was found in both farms throughout the fermentation. As well as, the yeast predominance from the genus Saccharomyces sp. and Hanseniaspora sp. for the Necoclí and Arauca farms, respectively. The above is taken as an indicator of the possible organoleptic differences found in the cocoas from each farm. Finally, with the biological groups identified, it was possible to estimate the microbiological incidences and the final properties of the cocoas evaluated.